Location Optimization of The Fighter Squadron in The National Air Defense System - Ar Rifky R, Hakim; Aprilia, Sherly; Riano, Gagat (Akademi Angkatan Udara, 2022)
This study uses the set covering problem (SCP) method to optimize the placement of the F-16 Fighting Falcon fighter in the national air defense system (Sishanudnas). Then the results of the SCP maximize the covering ability by minimizing the average distance between air bases with the P-Median Problem (PMP). The results of this study indicate that the Indonesian Air Force needs nine squadrons of F-16s, to be able to cover all of Indonesia's airspace. However, if the requirements are to include a base that currently operates fighter aircraft as a location for squadron placement, the Indonesian Air Force needs 11 squadrons of F-16 aircraft.